The use of new technologies among in-service Colombian ELT teachers * - McDougald, Jermaine (Colombian Applied Linguistics Journal, 2013)
This study reports on the impact of the Masters in English Language Teaching with an Emphasis on Autonomous Learning Environments from the Universidad de La Sabana. The report highlights how graduates from 12 cities from 9 departments throughout Colombia are using Information and Communication Technologies (ICT) for English language learning in order to promote autonomy. The data that has been gathered thus far reveals that teachers are becoming much more comfortable in evaluating ICT tools in accordance with their teaching context, the strengths and opportunities of ICT tools and their consequent improvement on language teaching, while promoting the development of autonomous learners.